Consumerism: A Study on the Evolution of the Consumer Movement - Rajanikanth, M. (Indian Journal of Marketing, 2011)
Consumerism is considered as a consumer movement which changed its face and meaning over a period of time. The Consumerism concept was there even before the term Consumerism coined to it. The concept of Consumerism was entered early in developed countries, which flowed in to developing countries. There is a lot of difference in the consumer movement and its implications between developed and developing countries. The level of consumer movement reflected the development of the country. In this article, the trends in consumerism over a period of time and the consumer movement in different countries are discussed.